The model of workforce agility dependent on drivers, strategies, practices, and results (2020)
For the time being, organizations throughout the world are in an environment that is constantly changing in various aspects including technological developments, customers’ preferences, emerging markets, and globalization. In this environment, the concept of agility, especially workforce agility is a valuable tool for organizations and can assist them considerably to cope with this situation. Given a substantial number of scholars have studied the concept of agility from the technical point of view up until now, and have neglected the human resource aspect, this study aims to, first of all, investigate the concept of workforce agility through a model incorporating drivers, practices, strategies advocating and stimulating the implementation of this concept and examine the relationships between these variables and second of all determine the results of implementing workforce agility system. The sample of the present study was selected from the staff and managers of the Ports and Maritime Organization of Iran, who had a bachelor's degree or higher and were working in the field of human resource management. Besides, we used a questionnaire to evaluate the variable. According to the findings, except for the relationship between drivers and implementation results all other relationships between drivers, practices, strategies, and results have been supported.